Korelasi antara Wanita, Perhiasan, dan Aurat dalam Al-Qur’an Surah An-Nur Ayat 31 Menurut Prespektif Mufassir Nusantara - Jannah, Miftahul (Lembaga Yasin AlSys, 2024)
In Islamic teachings regarding the relationship between jewelry and private parts, it has a big influence on women. Even the things that are attached to a woman, which are usually visible or invisible, are jewelry and it is an obligation to look after them, because if they are intentionally shown to someone who is not a mahram, it is tantamount to exposing one's private parts. Through Q.S an-Nur verse 31, the correlation between women, jewelry and private parts will be explained as well as the analysis of the views of Indonesian mufassir. This research uses a qualitative method, namely a method that focuses on data obtained by researchers from previous researchers. This research is also classified as a library research method. To further focus this research study, the author will further specify the interpretation of Indonesian commentators, namely Buya Hamka, Hasbi Ash-Shiddiqiey, and M. Quraish Shihab regarding the correlation between women, jewelry, and private parts in the Koran surah an-Nur verse 31 in the tafsir al-Azhar, an-Nur, and al-Misbah. This tafsir also uses the tahlili method with a bi al-ra'yi (reasoning/ijtihad) approach. In Q.S an-Nur verse 31, according to Buya Hamka, Hasbi Ash-Shiddiqiey, and M. Quraish Shihab, it is forbidden for a woman to show her private parts which are her jewelry. Don't show off the beauty of your body curves and protect your private parts from those who are not your mahram. Apart from that, because in general women's jewelry is only visible, such as decoration on their hands, face and feet, here the author feels it is necessary to discuss further about women's jewelry which is also their private parts, both visible and invisible.